Populism and nationalism revisited: A comparative study of the Spanish and Portuguese New Left. Issue 3 (26th January 2022) - da Silva, Filipe Carreira; Manucci, Luca; Veloso Larraz, David
Abstract: Current definitions of populism are insufficiently determinate. They fail to distinguish between populism and nationalism. We propose to remedy this problem by advancing a new definition of populism as the logic of democratic resentment. We apply this new definition to a comparison between Spain's Podemos and Portugal's Left Bloc (BE), which we classify as social carriers of populism. We make two contributions to the literature. First, our findings dispute existing characterisations of the Portuguese case, which fail to distinguish between populist and nationalist claim‐making. Second, our analysis undermines depictions of Podemos as the consummate populist party in Iberia: In 2015, the little studied BE was a stronger populist carrier than Podemos. The analytical framework underpinning this conclusion offers a more refined approach to populism than the alternatives and sets a higher standard for empirical replication.